2004
DOI: 10.2116/analsci.20.657
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Electrophoretic Behavior and Molecular Shapes of Aromatic Anions

Abstract: Capillary electrophoresis (CE) has been applied to the separation of various analyte ions. [1][2][3][4][5][6] Theoretically, the capillary electrophoretic mobility (µep) is calculated bywhere q, η and r are the electric charge of the ionized solute, the buffer viscosity and the solute radius, respectively. 7 Therefore, the CE separation of analyte ions is primarily dependent on the ionic charge and the ionic radius, unless there are any other interactions in the analyte ions, such as those with the capillary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Consequently, it was found that contribution of only the π-π interaction to the μepa values for the aromatic anions in the aqueous solution was very small. It was found that only the 9-AC that electro-migrates as its planar shape, 9 and has a relatively largely hydrophobic anthracene ring, produced the dimer ascribed to the π-π interaction, even in its small concentration region.…”
Section: Determination Of Dimerization Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it was found that contribution of only the π-π interaction to the μepa values for the aromatic anions in the aqueous solution was very small. It was found that only the 9-AC that electro-migrates as its planar shape, 9 and has a relatively largely hydrophobic anthracene ring, produced the dimer ascribed to the π-π interaction, even in its small concentration region.…”
Section: Determination Of Dimerization Constantsmentioning
confidence: 99%
“…It has been reported that some aromatic carboxylate ions migrated as a planar form in a capillary, compared to some aromatic sulfonate ions. 9 This observation suggests that the planar aromatic carboxylate ions would produce the π-π interaction between these aromatic rings in the electro-migration in CZE. Therefore, a capillary electrophoretic determination of the KD values for some aromatic carboxylate and sulfonate anions in an aqueous solution was investigated.…”
Section: Introductionmentioning
confidence: 99%